Management Strategy of Radio Republik Indonesia (RRI) Mataram in the Digital Era - Nimas Parista Pancawati; Yulanda Trisula Sidharta Yohanes; Lalu Ahmad Rahmat (Universitas Mataram, 2018)
RRI Mataram is an independent, neutral and non-commercial Public Broadcasting Institution that serves to provide information broadcasting, education, healthy entertainment, social control, and maintain a positive image of the nation in the international community. In the digital era, which was the era of media convergence, RRI Mataram did not escape from efforts to remain in the midst of society. This study aims to determine the management strategy of LPP RRI Mataram in the face of the digital era. This study uses a qualitative descriptive method with several steps, namely: Observation, interview, documentation, data analysis and conclusion. From the results of the study, the researchers formulated LPP RRI Mataram's management strategy using a SWOT analysis, including: understanding market share by presenting interesting and interesting shows to the community, maximizing and expanding networks of cooperation with various agencies, utilizing relations with the government, organizing programs for listeners, provide rewards for employees who excel, improve the quality of human resources by providing continuous training, conduct Joint Branding, add segmentation to program 2, improve program quality, and utilize other media as a medium to improve the existence of LPP RRI Mataram, and also complete broadcast systems with audio and video streaming, as well as fixing the RRI PLAY GO application, and minimizing technical problems with optimal device maintenance. Keywords: management strategy; radio; RRI Mataram; digital era